Klotho-derived peptide KP1 ameliorates SARS-CoV-2-associated acute kidney injury - Xu, Jie; Lin, Enqing; Hong, Xue; Li, Li; Gu, Jun; Zhao, Jinghong; Liu, Youhua (Frontiers in Pharmacology, 2024)
The severe cases of COVID-19, a disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), often present with acute kidney injury (AKI). Although old age and preexisting medical conditions have been identified as principal risk factors for COVID-19-associated AKI, the molecular basis behind such a connection remains unknown. In this study, we investigated the pathogenic role of Klotho deficiency in COVID-19-associated AKI and explored the therapeutic potential of Klotho-derived peptide 1 (KP1).We assessed the susceptibility of Klotho deficient Kl/Kl mice to developing AKI after expression of SARS-CoV-2 N protein. The role of KP1 in ameliorating tubular injury was investigated by using cultured proximal tubular cells (HK-2) in vitro and mouse model of ischemiareperfusion injury (IRI) in vivo.Results: Renal Klotho expression was markedly downregulated in various chronic kidney disease (CKD) models and in aged mice. Compared to wild-type counterparts, mutant KL/KL mice were susceptible to overexpression of SARS-CoV-2 N protein and developed kidney lesions resembling AKI. In vitro, expression of N protein alone induced HK-2 cells to express markers of tubular injury, cellular senescence, apoptosis and epithelial-mesenchymal transition, whereas both KP1 and Klotho abolished these lesions. Furthermore, KP1 mitigated kidney dysfunction, alleviated tubular injury and inhibited apoptosis in AKI model induced by IRI and N protein.These findings suggest that Klotho deficiency is a key determinant of developing COVID-19-associated AKI. As such, KP1, a small peptide recapitulating Klotho function, could be an effective therapeutic for alleviating AKI in COVID-19 patients.